Diccionario de regionalismos de la lengua española - Grosschmid, Pablo; Echegoyen, Cristina (Ed. Juventud, 1998)
Dictionary of Spanish language provincialisms from Spain and Latin America.
Keywords: Dialecten; Español - Provincialismos - América Latina - Diccionarios; Español - Provincialismos - Diccionarios; Español - Provincialismos - España - Diccionarios; Spaans; Mundart; Spanisch; Spanish language -- Provincialisms -- Dictionaries; Wörterbuch